Immune cells mediate the association between the plasma lipidome and pancreatic cancer: a Mendelian randomization analysis - Chunhong Ma; Dandan Liu; Changchun Ye; Zilu Chen; Ranran Kong; Jianzhong Li; Xuejun Sun; Zhengshui Xu (Scientific Reports)
Abstract The plasma liposome was associated with pancreatic cancer (PC) but the specific mechanism was still unclear. We aim to investigate the relationship between the plasma lipidome and PC risk, as well as the mediating roles of immune cells. Based on summary genome-wide association study (GWAS) statistics of 179 plasma lipidomes, 791 immune cells, and PC patients of European ancestry, two-sample MR analysis was utilized to identify the relationship between the lipidome and PC. Then, the two-step MR method was used to investigate the mediating role of immune cells and calculate the mediation effects. Sensitivity analysis was employed to evaluate the reliability of the findings. According to the inverse variance weighted (IVW) results, higher phosphatidylcholine (O−16:0_20:4) (P = 0.0248), phosphatidylinositol (18:0_20:4) (P = 0.0268), triacylglycerol (54:6) (P = 0.0415), and sterol ester (27:1/15:0) (P = 0.0138) levels reduced PC risk, while phosphatidylcholine (16:0_20:3) (P = 0.0295) and higher sphingomyelin (d40:1) (P = 0.0217) levels increased PC risk. Additionally, 22 immune cells had an effect on PC. Among those, only CD4 Regulatory T (Treg) AC cells played a mediating role between phosphatidylinositol (18:0_20:4) and PC (proportion mediated: 10.5%). No significant heterogeneity or pleiotropy was observed. The present study showed that PC risk was impacted by phosphatidylcholine, phosphatidylinositol, triacylglycerol, sterol ester, and sphingomyelin levels. The causal relationship between phosphatidylinositol (18:0_20:4) and PC was mediated by CD4 Treg AC cells, which provides insight for immunotherapy.